Linguistic Manifestations in the Commercialisation of Japanese Animation and Comics - Yoong, D.S.C.; David, M.K. (2010)
In today’s economic climate, capitalism is a central ideology that governs the market world. And this is no exception in the contemporary Japanese animation and comics (anime and manga) industry. Animators and artists have to evolve to meet the demands of the audience who are becoming more intellectually complex. To satisfy these needs, animators and artists have to use more sophisticated linguistic means. Fairclough’s (1995) who uses Foucault’s (1993) order of discourse refers to the ordered sets of discourse practices found in social domains, that is, the nexus of practices representing different discourses. For instance, in contemporary anime and manga, storylines may use multiple discourses, such as historical discourse (to refer to past events) and musical discourse (to build tension in the stories). This research examines the textual and intertextual use of historical discourse in two anime and manga titles, ‘Zipang’ and ‘Rurouni Kenshin’ using Fairclough’s (1995) CDA framework. This paper is part of larger study which focuses on five anime and manga titles as well as five types of discourses and their textual manifestations. Keywords: comics, animation, anime, manga, textual, intertextuality, discourse, critical discourse analysis